An RNA/DNA hybrid origami-based nanoplatform for efficient gene therapy. Issue 30 (22nd July 2021) - Wu, Xiaohui; Liu, Qing; Liu, Fengsong; Wu, Tiantian; Shang, Yingxu; Liu, Jianbing; Ding, Baoquan
Abstract : An RNA/DNA origami-based nanoplatform was designed for efficient antisense delivery to silence target gene without any transfection reagents in eukaryotic cells. Abstract : Nucleic acid nanostructures are promising biomaterials for the delivery of homologous gene therapy drugs. Herein, we report a facile strategy for the construction of target mRNA (scaffold) and antisense (staple strands) co-assembled RNA/DNA hybrid "origami" for efficient gene therapy. In our design, the mRNA was folded into a chemically well-defined nanostructure through RNA–DNA hybridization with high yield. After the incorporation of an active cell-targeting aptamer, the tailored RNA/DNA hybrid origami demonstrated efficient cellular uptake and controllable release of antisenses in response to intracellular RNase H digestion. The biocompatible RNA/DNA origami (RDO) elicited a noticeable inhibition of cell proliferation based on the silencing of the tumor-associated gene polo-like kinase 1 (PLK1). This RDO-based nanoplatform provides a novel strategy for the further development of gene therapy.